2005
DOI: 10.1002/ijc.21240
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response to a non‐conserved C‐terminal part of human histone deacetylase 3 in colon cancer patients

Abstract: Antibodies to cancer antigens can often be detected in the sera of patients, although the mechanism of the underlying humoral immune response is poorly understood. Using immunoscreening of tumor-derived cDNA expression libraries (SEREX), we identified human histone deacetylase 3 (HDAC3) as serologically defined antigen in colon cancer. Closely related HDAC1 and HDAC2 do not elicit humoral response in colon cancer patients. We show that the C-terminal region of HDAC3 protein lacking the homology to other Class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…HDAC2 expression is increased in human colon cancer, in which there is a loss of APC tumor suppressor (19). HDAC3 expression is increased in human tumor samples of colon cancer compared with normal tissue (18,20). HDAC5 is downregulated in colon cancer (21).…”
Section: Introductionmentioning
confidence: 99%
“…HDAC2 expression is increased in human colon cancer, in which there is a loss of APC tumor suppressor (19). HDAC3 expression is increased in human tumor samples of colon cancer compared with normal tissue (18,20). HDAC5 is downregulated in colon cancer (21).…”
Section: Introductionmentioning
confidence: 99%
“…This finding provides an interesting possible functional explanation for the long known interlink between nutrition and colorectal cancer formation. Finally, the detection of antibodies directed against HDAC3 has been suggested as a serologic antigen/biomarker for colorectal cancer (15).…”
mentioning
confidence: 99%
“…Of the 5 SEREX-based antigens examined in this study, serum samples from colorectal cancer patients reacted to rCCCAP with the highest frequency (35.1%) and to rNY-CO-16 with the lowest frequency (18.1%). Similarly, Scanlan et al 34 demonstrated a frequency of serological response to 13 colorectal cancer-related antigens of 3-8% and Shebzukhov et al 37 identified HDAC3 as a novel serological antigen for colon cancer detection with a 5% serological response frequency. A compilation of anti-p53 studies indicates the reaction frequency among colorectal cancer patient serum samples was 15-24.6%.…”
Section: Discussionmentioning
confidence: 97%